IT Audit with ITIL on Business Process, Application and IT Infrastructure in Bali Rattan Bag - Ni Luh Ade Mita Rahayu Dewi (International Journal of Engineering and Emerging Technology, 2021)
This study discusses information technology audits using the Information Technology Infrastructure Library framework. The case study used in this research is the Bali Rattan Bag, namely the Bali Rattan Bag which is a business engaged in the production and sale of rattan-based bag products. Bali Rattan Bags was founded in 2019. The research was carried out in accordance with the business processes carried out in Bali Rattan Bags. In this study, researchers used survey data collection methods, interviews, and literature study. The survey was conducted by distributing questionnaires. The questionnaire was chosen because it can represent the voices of several people about something and later the results of the questionnaire can be calculated to get the desired results. This study uses an audit with the Information Technology Infrastructure Library (ITIL) framework. The use of ITIL will improve information technology services and improve operational performance. The focus of this research is on the operational domain of services, business processes, applications, and infrastructure in IT services in the Bali Rattan Bag. The purpose of this study was to determine the performance of information technology services in Bali Rattan Bags and provide suggestions based on the analysis results according to ITIL standards for improvement and improvement of information technology services. Index Terms— Audit, Information Technology Infrastructure Library, ITIL Framework